Navigating Black Identity Development: The Power of Interactive Multicultural Read Alouds with Elementary-Aged Children - Rebekah E. Piper (MDPI AG, 2019)
Racial identity development in young children is influenced by interactions with teachers and curriculum in schools. This article, using the framework of critical race theory, critical literacy, and critical pedagogy, explores how three elementary-aged Black children view their own identity development. Specifically, observing how children interact with Movement-Oriented Civil Rights-Themed Children’s Literature (MO-CRiTLit) in the context of a non-traditional summer literacy program, Freedom Schools, to influence their Black identity. Professional development and preservice teacher preparation are needed to support teachers as they navigate through learning about pedagogical practices that increase student engagement.